Banking financial accessibility among traditional market traders in Brastagi City / Nisrul Irawati and Friska Sipayung - Irawati, Nisrul; Sipayung, Friska (2017)
Traditional market always considered as a part of small marginalized community although they play an important role to develop economic of a developing country. As Business development will possible develop if the business gains an easy access for the source of fund. Source of fund play an important role in managing business that can be come from variety sources of external fund but in this study focused on source of fund from formal Banking. Traditional market is one of the forms of SME (Small Medium Entepries). This study aims in mapping the condition of banking financial accessibility in traditional market with 120 respondents in Brastagi City, Indonesia. There are several factors that can be used to measure the banking financial accessibility that is access to formal banking services, access to transaction, access to savings, access to credit/loan. The research found that most of the traditional market traders have an account in banking institution but they do not used credit/overdraft because they tend to use their owned wealth in order to finance the business activity. The traditional markets traders can be implied to be in low degree of financial accessibility although almost of them have an account but only a few of the traditional market traders have an access to the line of credit or overdraft.